Technological approaches to the reuse of demolition waste in road construction and their environmental benefits - Sorochynska, Olena; Khrutba, Viktoriia; Rutkovska, Inessa (International Conference “Environmental Engineering”, 2026)
The study examines reviews modern technological approaches to the reuse of construction and demolition waste in road construction, specifically the application to produce asphalt and concrete materials. It analyzes methods of mechanical and chemical processing, recycling technologies, and their integration into the structural layers of pavement. Particular attention is paid to the environmental benefits of such solutions: waste reduction, decreased consumption of natural resources, and lower emissions of greenhouse gases and pollutants. The research highlights practical aspects of using reclaimed materials and assesses their technical performance in comparison with virgin materials. The findings confirm the effectiveness of implementing waste reuse technologies for the sustainable development of transport infrastructure.